Espetáculos per(formáticos) abalam as fronteiras da cidade sub(versiva) - Nery, Vívian Carla Reis (2018)
The streets, the alleys, the sidewalks and the soles of the worn shoe. Like this the dissertation is being reassembled, with the main objective of mapping the boundary bodies of the third margin, FRAMED windows and not FRAMED. Felipe de Jesus subject / researcher brings to the surface the camouflage through the city images. About these wanderings are presented scenes disassembling the dissident show. City and school it converges announcing the cartography, emerging to the surface performativities and denouncing the intersectionalities destructing the enclosures, the research is weaving the disqualifications, in which, entangle and reassemble wandering crossings. The mall, the restrooms, and the bus are disconcerting the flowing-rhizomatic and the functions and the acts of camouflage performativity that occupy the scene in the spectacular city and perhaps their sub(versive) and / or normative bodies. In this way, we will re-arrange our theoretical cut through the poststructuralist debates of the studies Queer, gender, cultural, and Deleuze rhizomes.